2013
DOI: 10.1556/jfc-d-12-00025
|View full text |Cite
|
Sign up to set email alerts
|

Important Industrial Procedures Revisited in Flow: Very Efficient Oxidation and N-Alkylation Reactions with High Atom-Economy

Abstract: The atom economy concept is one of the earliest recognition for green and sustainable aspects of organic synthesis. Over the years, novel technologies emerged that made this important feature of reactions into practice. Continuousflow devices increased the efficiency of the chemical transformations with novel process windows (high T, high p and heterogeneous packed catalysts etc.) and increased safety which turned the attention to reexamine old, industrial processes. Oxidation can be performed under flow catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Former attempts with a similar flow system showed that reaction temperature below 200°C produces predominantly N-alkylated products [25]. These observations led to the conclusion that cleavage of the carbon-hydrogen bond might require higher temperature.…”
Section: Resultsmentioning
confidence: 98%
“…Former attempts with a similar flow system showed that reaction temperature below 200°C produces predominantly N-alkylated products [25]. These observations led to the conclusion that cleavage of the carbon-hydrogen bond might require higher temperature.…”
Section: Resultsmentioning
confidence: 98%
“…However, there are severe flammability and explosive hazards associated with aerating organic solvents, which must be overcome before they can be implemented industrially. More recently, 1% Au/TiO 2 was utilized using the same system for the oxidation of 1-phenyl ethanol to the corresponding ketone in a single-pass mode (Table 1.3, entry 2) [69]. Taking advantage of the small reactor volume of a catalyst cartridge offered by a X-Cube reactor, aerobic oxidation of primary and secondary alcohols to aldehydes and ketones can be achieved using Ru/Al 2 O 3 as catalyst [68].…”
Section: Oxidationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Micromixing, efficient heat transfer in tubular reactors having a high surface-to-volume ratio and enhanced safety due to the small size of reactors are some of the most salient benefits of continuous flow chemistry compared to traditional batch processes. [10][11][12][13] As a result, flow approaches in synthetic chemistry rapidly thrives in academic and industrial laboratories [14][15][16][17][18] and affords considerable opportunities to develop novel transformations and access new reactivities under unusual experimental conditions. [19][20][21][22][23][24] Both, deep mechanistic understanding and optimization of complex synthetic transformations conducted either in flow or in batch modes, require the use of suitable analytical technologies.…”
Section: Introductionmentioning
confidence: 99%